Some existence, uniqueness results on positive solutions for a fractional differential equation with infinite-point boundary conditions - Zhai, Chengbo; Wang, Li (Nonlinear Analysis: Modelling and Control, 2017)
We investigate a class of Riemann–Liouville’s fractional differential equation with infinite-point boundary conditions. We give some new properties of the Green’s function associated with the fractional differential equation boundary value problem. Based upon these new properties and by using Schauder’s fixed point theorem, we establish some existence results on positive solutions for the boundary value problem. Further, by using a fixed point theorem of general concave operators, we also present an existence and uniqueness result on positive solutions for the boundary value problem.